Searching for People and Accompanying them on their Journey Back - Wanat , Zbigniew (Studia Gdańskie, 2018)
The post-synodal exhortation Amoris laetitia of Pope Francis provoked the most heated theological dispute since the Second Vatican Council. They also awakened new hopes and expectations of the faithful, especially those living in non-sacramental relationships. Because of objective spiritual obstacles, they cannot receive absolution and receive Holy Communion. Now, because of these aroused hopes, they turn again to priests, especially to confessors. It is a great challenge for them to meet all those who need help and accompaniment on their way back to full integration with the community of the Church. An important impulse for reflection on this challenge is Pastoral Guidelines for Exhortation Amoris laetitia adopted by the Polish Episcopal Conference at its 379th plenary meeting on 8 June 2018. This document was long awaited by the priests. He have provided answers to some questions concerning the pastoral practice of the Church, in particular concerning the giving of Holy Communion to people living in non-sacramental relationships. Bishops reminded the already existing indications, which have not changed. On the other hand, they placed a strong emphasis on a renewed evangelical attitude towards people in an irregular situation. They emphasized that the pastoral ministry should be characterize “with closeness, respect and compassion, which at the same time heal, liberate and encourage adolescence in the Christian life”. With regard to this pastoral goal, the author of the article will focus on the role and selected tasks of the priest. This will be a welcoming reception, accompaniment in the discernment of situations and a gradual integration with the community of the Church.